2016
DOI: 10.1002/brb3.487
|View full text |Cite
|
Sign up to set email alerts
|

Statin use after intracerebral hemorrhage: a 10‐year nationwide cohort study

Abstract: IntroductionAlthough statin therapy is beneficial to patients with ischemic stroke, statin use, and intracerebral hemorrhage (ICH) remain a concern. ICH survivors commonly have comorbid cardiovascular risk factors that would otherwise warrant cholesterol‐lowering medication, thus emphasizing the importance of assessing the characteristics of statin therapy in this population.MethodsWe performed a cohort study by using 10 years of data collected from the National Health Insurance Research Database in Taiwan. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…606,612 However, other observational, nonrandomized studies have not found this association in patients with hypercholesterolemia, and risk may depend on the patient risk for recurrent ICH and type of statin used. 607,609,613–618 For both classes of medications, the indications and risk-benefit profiles for an individual patient must be weighed. NSAID use is associated with an increased risk of bleeding 610,611 ; thus, regular long-term use should be avoided when possible in patients with ICH.…”
Section: Preventionmentioning
confidence: 99%
“…606,612 However, other observational, nonrandomized studies have not found this association in patients with hypercholesterolemia, and risk may depend on the patient risk for recurrent ICH and type of statin used. 607,609,613–618 For both classes of medications, the indications and risk-benefit profiles for an individual patient must be weighed. NSAID use is associated with an increased risk of bleeding 610,611 ; thus, regular long-term use should be avoided when possible in patients with ICH.…”
Section: Preventionmentioning
confidence: 99%
“…The "Stroke Prevention by Aggressive Reduction in Cholesterol Levels" (SPARCL) trial initially raised concern that statins might increase the risk for future ICH among patients with previous ischemic stroke or ICH [160]. While some studies also suggested an increased recurrent ICH risk in ICH survivors using statins [160][161][162][163], others suggest that statins used acutely are associated with improved mortality and functional outcome [164,165]. A recent meta-analysis of statin use in stroke survivors found no evidence that statin use in ICH survivors increases future ICH; there was a small increased risk of ICH after ischemic stroke; however, the strongest finding was that in all stroke survivors (ischemic stroke or ICH) there was a substantial and significant improvements in mortality and functional outcomes among statin users [166].…”
Section: Statin Therapymentioning
confidence: 99%
“…Additionally, the intensity of statin use had no significant relationship with recurrent ICH or other secondary adverse outcomes. Additional prospective randomized clinical trials are required to confirm the favorable effects of hydrophilic statin therapy in ICH patients (Tai, Lin & Lee et al 2016). According to study in animal, simvastatin and atorvastatin treatment for 1 week after ICH significantly improved neurological outcome and reduced hematoma volume and tissue loss at 4 weeks.…”
Section: Resultsmentioning
confidence: 99%